Analisis Teknik Sashiko Pada Busana Pesta dengan Motif Menara Pinisi UNM - Asiani Abu; Rika Riwayani; Nurhijrah (Universitas Negeri Makassar, 2023)
This research is an engineering research that aims to: 1) Know the party dress design using the pinisi tower idea as the source motif, 2) Know the process of making party dress techniques, 3) Know the steps in the process of making Sashiko Technique Motifs with the pinisi tower idea source 4) Know the opinion of the panelists about the result of the party dress using the motif of the Finish Tower idea. The data collection instruments used were Focus Group Discussion (FGD), observation and documentation. The results showed that: 1) The party dress design with the pinisi tower motif uses the H silhouette of the overalls and has a prinses line on the front where the line reaches the bottom, on the right side there is a pinisi tower motif as well as on the chest and upper back with embroidery using the Sashiko technique, has smooth sleeves, shanghai collar and back zipper, 2) The technique for making party dresses begins with designing, making patterns, designing materials, cutting, sewing clothes, embroidering motifs to the finishing stage 3). Making the Sashiko technique for party attire using the pinisi tower idea source motif, carried out by preparing tools and materials to make embroidery with the shasiko technique using embroidery thread that matches the pinisi tower motif color 4) Panelist opinion on the results of the party dress using the Sashiko embroidery technique and motifs Pinisi tower ideas are in the very good category with an average score of 92,5%.